Actin-microtubule cytoskeletal interplay mediated by MRTF-A/SRF signaling promotes dilated cardiomyopathy caused by LMNA mutations - Le Dour Caroline; Chatzifrangkeskou Maria; Macquart Coline; Magiera Maria M.; Peccate Cécile; Jouve Charlène; Virtanen Laura; Heliö Tiina; Aalto-Setälä Katriina; Crasto Silvia; Cadot Bruno; Cardoso Déborah; et al. (Nature Research, 2025)
Mutations in the lamin A/C gene (LMNA) cause dilated cardiomyopathy associated with increased activity of ERK1/2 in the heart. We recently showed that ERK1/2 phosphorylates cofilin-1 on threonine 25 (phospho(T25)-cofilin-1) that in turn disassembles the actin cytoskeleton. Here, we show that in muscle cells carrying a cardiomyopathy-causing LMNA mutation, phospho(T25)-cofilin-1 binds to myocardin-related transcription factor A (MRTF-A) in the cytoplasm, thus preventing the stimulation of serum response factor (SRF) in the nucleus. Inhibiting the MRTF-A/SRF axis leads to decreased α-tubulin acetylation by reducing the expression of ATAT1 gene encoding α-tubulin acetyltransferase 1. Hence, tubulin acetylation is decreased in cardiomyocytes derived from male patients with LMNA mutations and in heart and isolated cardiomyocytes from Lmnap.H222P/H222P male mice. In Atat1 knockout mice, deficient for acetylated α-tubulin, we observe left ventricular dilation and mislocalization of Connexin 43 (Cx43) in heart. Increasing α-tubulin acetylation levels in Lmnap.H222P/H222P mice with tubastatin A treatment restores the proper localization of Cx43 and improves cardiac function. In summary, we show for the first time an actin-microtubule cytoskeletal interplay mediated by cofilin-1 and MRTF-A/SRF, promoting the dilated cardiomyopathy caused by LMNA mutations. Our findings suggest that modulating α-tubulin acetylation levels is a feasible strategy for improving cardiac function.